Determining interest and use of fintech in Syariah Banks in Indonesia (Case study on Syariah Bank Indonesia (BSI)) - Indrarini, Rachma; Syam, Nur; Fitrianto, Achmad Room (Technium Business and Management, 2025)
The purpose of this study is to look at the determining factors of mobile banking usage in Islamic banks in Indonesia, especially at Bank Syariah Indonesia. The method used in this study is a factor analysis study, namely the EFA (Exploratory Factor Analysis) technique. The data comes from active customers who use Bank Syariah Indonesia mobile banking throughout Indonesia. The findings of the study suggest that Based on the research results, it can be concluded that there are two new factors formed in the factors that determine the interest and use of mobile banking in Fintech at Bank Syaraiah in Indonesia (case study at BSI). These factors are the Main Factors and Supporting Factors. This research is hoped to have implications for the use of mobile banking by Islamic banks in Indonesia and it can be a guideline for Islamic banks in improving the quality of their technology. To the best of the authors' knowledge, this is the first research related to the use of mobile banking in Indonesia using EFA (Exploratory Factor Analysis).